Individual and Relationships: The "Deepened" Spirituality in Philip Teng’s Thought - NIU, Buxiao (Journal of Research for Christianity in China (JRCC), 2025)
Philip Teng’s spiritual perspective revolves around the concept of "Deepened," emphasizing spirituality as a dynamic and relational practice that unites inner renewal with outward testimony through daily living. Teng’s approach moves beyond the static or fixed notions of spirituality often seen in traditional Chinese churches, advocating instead for growth through repentance, self-denial, and union with Christ. This study systematically examines Teng’s major works and sermons, employing textual analysis and historical interpretation to uncover the theoretical foundations and practical strategies underlying his spirituality. Key areas of focus include his experiential epistemology, his use of negative theology, and his insights into the relationship between spirituality and mental health. Furthermore, Teng highlights the inseparability of spirituality and psychological growth, advocating practical methods such as the "School of Spirituality," "Rest," and "Fasting Prayer" to provide a holistic pathway for spiritual and mental development. His teachings offer contemporary Chinese churches essential guidance for pastoral care, helping believers shift away from idealized spiritual aspirations and instead cultivate a grounded, actionable, and transformative faith practice.